Spacing and movement in the green porcelain crab Petrolisthes armatus: evidence for male competition and mate guarding. Issue 2 (4th March 2017) - Wassick, Ann; Hughes, Melissa; Antonio Baeza, J.; Fowler, Amy; Wilber, Dara
Abstract: The green porcelain crab, Petrolisthes armatus, is a common invasive species on inter-tidal oyster reefs in the South Atlantic Bight whose behavior is largely unknown. We assessed the effects of the presence of opposite-sex conspecifics on adult crab spacing at a low density to infer potential mate acquisition behaviors. Adult crabs held in all-male, all-female, and mixed-sex treatments were observed twice daily over five days to determine nearest-neighbor (NN) distances and relative activity. Males in the mixed-sex treatment with the shortest NN distances (NN1 ) were most commonly (1) closest to females, and, when compared to NN1 males in the all-male treatment, were (2) closer to their NN and (3) had lower activity levels. Female movement did not differ between treatments. Percent ovigerous females at the end of trials were higher in the mixed-sex treatment, reflecting mating activity, which when observed, involved inter-molt females. Mate guarding, rather than pure-searching behavior, was the mating behavior most consistent with observed spacing and movement patterns.